2019
DOI: 10.1111/jfb.14151
|View full text |Cite
|
Sign up to set email alerts
|

Feeding studies take guts – critical review and recommendations of methods for stomach contents analysis in fish

Abstract: Studies on the feeding ecology of fish are essential for exploring and contrasting trophic interactions and population and community dynamics within and among aquatic ecosystems. In this respect, many different methods have been adopted for the analysis of fish stomach contents. No consensus has, however, been reached for a standardised methodology despite that for several decades there has been an ongoing debate about which methodical approaches that should be preferred. Here, we critically review and scrutin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
101
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 160 publications
(102 citation statements)
references
References 73 publications
0
101
0
1
Order By: Relevance
“…Recently, DNA metabarcoding has emerged as a useful technique to study the trophic ecology of several organisms 22 24 . However, these techniques are not so often combined with other methods to enhance their utility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, DNA metabarcoding has emerged as a useful technique to study the trophic ecology of several organisms 22 24 . However, these techniques are not so often combined with other methods to enhance their utility.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of potential prey stable isotope signatures (imperative to estimate the assimilated diet), they still provide useful information about trophic position, isotopic width and overlap, as a proxy of trophic niche width and overlap between species 36 , 37 . Thus, the combination of different techniques can provide new insights and show a general overview of the feeding ecology of organisms 22 (Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Only amphipods, insect larvae, zooplankton, and fish were considered for the stomach‐parasite analysis, as they are the potential intermediate hosts of the identified intestinal parasites. The importance of these prey in the fish was expressed as frequency of occurrence (Amundsen & Sánchez‐Hernández, 2019). The dietary information from the individual stomach samples was incomplete due to a high number of empty stomachs (Arctic charr N = 115, brown trout N = 29), especially during winter‐time.…”
Section: Methodsmentioning
confidence: 99%
“…Smiroldo et al [80] revealed that the frequency of occurrence of amphibians in dietary studies in Eurasian otters averaged 12%. Considering that the frequency of occurrence only covers the total number of stomachs with prey and thus without taking the relative abundance of each prey type into account [119], it is doubtful that the use of literature sources only including frequency of occurrence can draw conclusions regarding the importance of salamanders as energy resources for otter species compared to papers reporting the abundance (numerical, biomass, or volume) of prey categories. Salamanders commonly represent a small portion of the stomach contents in brown trout and northern pike (Exos lucius) [54,77,78], which underscores the small importance of salamanders as energy subsides for piscivorous fish species such as, for example, many salmonid and pike species.…”
Section: Salamanders As Energy Subsides For Higher Trophic Levelsmentioning
confidence: 99%